Board Certified Physicians in Health Informatics A European Precedent for Professional Recognition - France, F.H. Roger; Beguin, Cl.; Mélot, Ch.; Gillet, P. (Yearbook of Medical Informatics, 2010)
Objective: To document the official recognition of a new specialty in health informatics in one European country, because a similar legal process may lead to professional equivalence for physicians in all member countries of the European Union and elsewhere.Method: In Belgium, a Ministerial Decree in 2001 established criteria for the certification of Physician Specialist in Health Data Manage- ment. Such recognition of a new competence is a natural comple- ment to a University Master’s degree and can have a major influence on the salary scale and on professional recognition and develop- ment in public and private sectors.Results: Teaching and training programmes in Belgium were adapted according to the Decree. Ninety-seven physicians were certi- fied in the French community and 72 in the Flemish community be- tween 2002 and 2009, with a prerequisite of this title for engage- ment in several official and private positions, and a salary increase.Discussion In other countries, recognition of a specific competence in health informatics remains, at best, a voluntary registration proc- ess and University programs vary widely. The implications of this Decree, with recognition of Physician Specialist in Health Data Man- agement as a special competence, rather than a medical specialty, are discussed. The extension of such recognition to health profes- sions other than physicians is not yet envisaged.Conclusion: Although the title “Physician Specialist in Health Data Management” may appear rather old fashioned, recognition of this competence in a European Union country is a first step to help its diffusion to other countries.
Keywords: Board certification; salary scale; education; health informatics; data management